Determinação da relação dos aminoácidos essenciais para juvenis de tilápia-do-Nilo, pelo método da deleção - Diógenes, Alexandre Firmino [UNESP] (2013)
The aim of this study was to determine the optimal ratio of the main limiting amino acids in the diet, by deletion method, for juvenile Nile tilapia GIFT strain. Fishes with an initial weight ± 20.0 g were conditioned for 57 days in tanks (1500 L) with recirculating water system. Fed three times a day (08:00am, 12:00pm and 4:00pm) with diets based on amino acid composition and Furuya (2010). The positive control diet formulated had all the requirements for fishes, and the other made by diluting this with corn starch, had a 45% of deficiency. With the exception of the amino acid test, the other amino acids in the diet were supplemented with synthetic amino acids at the same concentration of positive control diet (100%). A completely randomized design with 11 treatments and 4 replications taken two at a time was used. The determination of the optimum ratio was based on the regression line between group test, whose limiting amino acid provided the greatest reduction in nitrogen retention and the control group, drawing a straight line until it reaches the plateau formed by the retention provided by positive control diet, according to the method used by Wang & Fuller (1989). Thus, the control treatment had the highest weight gain, resulting in higher nitrogen deposition. The ideal ratio of essential amino acids, expressed relative to lysine (=100)/estimated rate of amino acid was: methionine, 64; threonine 94, tryptophan 24, arginine 126, histidine, 34, isoleucine 57, leucine 96, valine and, 76